RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND ANEMIA IN ADOLESCENT GIRLS AT SMPN Y, BOGOR REGENCY - Rohayati, Rohayati; Sofiyatul Fuadah, Elsi (Jurnal Mitra Kesehatan, 2026)
Introduction : Iron-deficiency anaemia remains a major public health challenge among adolescent girls in Indonesia. Although nutritional status is recognized as an important determinant of health, both undernutrition and overnutrition may disrupt iron metabolism and increase the risk of anaemia. This study aimed to examine the association between nutritional status and anaemia among adolescent girls at SMPN Y, Bogor.Method: The study used a cross-sectional design, sampling 220 adolescent girls aged 12–16 years. Nutritional status, measured by Age-Adjusted Body Mass Index (BMI-for-Age), was categorised as Non-Overweight or Overweight/Obese, while anaemia status was determined by haemoglobin (Hb) levels. Bivariate data analysis used the Pearson Chi-Square test and odds ratio (OR) estimation at a 95% confidence level. Result: The prevalence of anaemia among adolescent girls was 29.1%. Most respondents (67.7%) had a non-overweight nutritional status. Statistical analysis indicated no significant association between nutritional status (BMI-for-age) and anaemia (p-value = 0.399; p > 0.05). Adolescent girls with a non-overweight nutritional status had a 1.315-fold higher risk of developing anaemia compared to those in the overweight or obese group (OR = 1.315; 95% CI: 0.695–2.488). Conclusion: Nutritional status is not statistically significantly associated with anaemia in adolescent girls. It is recommended that intervention programmes should not focus solely on underweight adolescents, but instead conduct comprehensive haemoglobin screening regardless of anthropometric status and strengthen monitoring of compliance with iron tablet consumption in schools.